2013
DOI: 10.1093/molehr/gat091
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of autophagy by mTOR is associated with abnormal apoptosis in ovarian endometriotic cysts

Abstract: Mammalian target of rapamycin (mTOR) is known to be a major negative regulator of autophagy. Recent studies have shown that mTOR activity is abnormally increased in endometriotic lesions. In endometriosis, abnormal mTOR activity may contribute to the alteration of endometrial cell autophagy, which may affect apoptosis because endometrial cell autophagy is directly involved in the regulation of apoptosis. To test this hypothesis, we investigated whether endometrial cell autophagy is altered by aberrant mTOR act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 47 publications
6
58
1
1
Order By: Relevance
“…However, endometriotic cells have been shown to respond abnormally to ovarian steroids, which contributes to the dysregulation of autophagy in these cells (22). Consistent with this finding, our results showed that progesterone treatment did not affect the induction of autophagy in estrogen-treated ECSCs, suggesting that aberrant autophagy induction in endometriotic cells may be associated with the subnormal response to progesterone known as progesterone resistance.…”
Section: Figuresupporting
confidence: 88%
See 4 more Smart Citations
“…However, endometriotic cells have been shown to respond abnormally to ovarian steroids, which contributes to the dysregulation of autophagy in these cells (22). Consistent with this finding, our results showed that progesterone treatment did not affect the induction of autophagy in estrogen-treated ECSCs, suggesting that aberrant autophagy induction in endometriotic cells may be associated with the subnormal response to progesterone known as progesterone resistance.…”
Section: Figuresupporting
confidence: 88%
“…The therapeutic mechanisms of progestin may include antiovulatory activity, resulting in reduced serum E levels (10), and/or direct antiproliferative and anti-inflammatory effects on endometriotic cells (39)(40)(41). However, it is still unclear whether progestin directly affects the induction of autophagy in endometriotic cells, although autophagy is known to be involved in the pathogenesis of endometriosis by affecting apoptosis (22). Therefore, to elucidate the therapeutic mechanisms of progestin, we evaluated the effects of dienogest on the induction of autophagy in endometriotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations